Women’s Education and Social Reform in India: Creating ‘Angels in the House?’ - Pappu, Rekha (Voices of Teachers and Teacher Educators, 2019)
This article discusses the various aspects involved in the process of introducing women’s education in India during the social reform period of the 19th century. It focuses on the developments with regard to women’s education during this period both within the Hindu and the Muslim communities. Available literature on social reform is used to track the nuances of the approaches adopted by the reformers to introduce and strengthen women’s education within the two major religious communities, i.e. Hindus and Muslims. The article further goes on to draw attention to the commonalities and differences in the manner in which the question of women’s education within the two communities was addressed.